Answer:
Explanation:
From the figure attached,
CP is an angle bisector of angle BCD and BP is the angle bisector of angle CBE
Therefore, m∠DCP ≅ m∠BCP
and m∠PBE ≅ m∠PBC
m∠A + m∠CBA = m∠BCD
m∠A + (180° - m∠CBE) = m∠BCD
m∠A + 180° = m∠CBE + m∠BCD
m∠A + 180° = 2(m∠PCB) + 2(m∠PBC) [Since m∠CBE = 2m∠PCB and m∠BCD = 2(m∠PBC)
m∠A + 180° = 2(m∠PCB + m∠PBC)
m∠A + 180° = 2(180° - m∠BPC) [Since m∠PCB + m∠PBC + m∠BPC = 180°]
![[(1)/(2)(m\angle A)]+90=180 - m\angle BPC](https://img.qammunity.org/2021/formulas/mathematics/high-school/cqnrmgzyzm24jmmvh0b3538yeogruv6kq7.png)
m∠BPC = 180 -
![[(1)/(2)(m\angle A)]-90](https://img.qammunity.org/2021/formulas/mathematics/high-school/xhfiqcbu76odq5n9tpoeudxyuoaq2ahfjm.png)
m∠BPC = 90 -
![(1)/(2)m\angle A](https://img.qammunity.org/2021/formulas/mathematics/high-school/wmhbjm6wo2ic35f8rtaebq2f0ddzdrlf3w.png)